Different patterns of colonization of Oxalis alpina in the Sky Islands of the Sonoran desert via pollen and seed flow. Issue 11 (27th April 2018) - Pérez‐Alquicira, Jessica; Weller, Stephen G.; Domínguez, César A.; Molina‐Freaner, Francisco E.; Tsyusko, Olga V.
Abstract: Historical factors such as climatic oscillations during the Pleistocene epoch have dramatically impacted species distributions. Studies of the patterns of genetic structure in angiosperm species using molecular markers with different modes of inheritance contribute to a better understanding of potential differences in colonization and patterns of gene flow via pollen and seeds. These markers may also provide insights into the evolution of reproductive systems in plants. Oxalis alpina is a tetraploid, herbaceous species inhabiting the Sky Island region of the southwestern United States and northern Mexico. Our main objective in this study was to analyze the influence of climatic oscillations on the genetic structure of O. alpina and the impact of these oscillations on the evolutionary transition from tristylous to distylous reproductive systems. We used microsatellite markers and compared our results to a previous study using chloroplast genetic markers. The phylogeographic structure inferred by both markers was different, suggesting that intrinsic characteristics including the pollination system and seed dispersal have influenced patterns of gene flow. Microsatellites exhibited low genetic structure, showed no significant association between geographic and genetic distances, and all individual genotypes were assigned to two main groups. In contrast, chloroplast markers exhibited a strong association between geographic and genetic distance, had higher levels of genetic differentiation, and were assigned to five groups. Both types of DNA markers showed evidence of a northward expansion as a consequence of climate warming occurring in the last 10, 000 years. The data from both types of markers support the hypothesis for several independent transitions from tristyly to distyly. Abstract : In this study, we assess the impact of climatic oscillations on the genetic structure of Oxalis alpina and the evolutionary transition from tristylous to distylous reproductive systems in the Sky Islands region. The phylogeographic structure among O. alpina populations was inferred based on microsatellite data and compared to that of the chloroplast DNA data. Despite the reduced genetic differentiation identified for microsatellites compared to cpDNA, both types of DNA markers showed evidence for colonization via a northward expansion as the result of climate warming occurring in the last 10, 000 years. In addition, the data from both markers support the hypothesis for several independent transitions from tristyly to distyly.